2020
DOI: 10.4102/sajcd.v67i1.702
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical number inflection in Arabic-speaking children and young adults with Down syndrome

Abstract: Background: Individuals with Down syndrome (DS) have more difficulties with the structural aspects of language, including morphology (concatenation and non-concatenation) and syntax (word order and grammatical/concord rules), than with other language components (e.g. vocabulary, phonetics and pragmatics).Objectives: This study investigates the accuracy of grammatical number inflection produced by Jordanian Arabic-speaking children and young adults with DS. The work also examines the correlation between age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Therefore, our hypothesis has been confirmed once again, thus enhancing the findings of previous research investigating the accuracy of grammatical number inflection produced by children with Down syndrome. According to these findings, children with Down syndrome scored lower in the dual and plural forms of nouns than in the singular ones (Mashaqba et al., 2020). However, our findings contradict those of Ring and Clahsen (2005), who proposed that English‐speaking adolescents with Down syndrome (aged 12–14 years) performing several elicitation tasks on past tense and noun plural inflection displayed no signs of a specific deficit in inflectional morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our hypothesis has been confirmed once again, thus enhancing the findings of previous research investigating the accuracy of grammatical number inflection produced by children with Down syndrome. According to these findings, children with Down syndrome scored lower in the dual and plural forms of nouns than in the singular ones (Mashaqba et al., 2020). However, our findings contradict those of Ring and Clahsen (2005), who proposed that English‐speaking adolescents with Down syndrome (aged 12–14 years) performing several elicitation tasks on past tense and noun plural inflection displayed no signs of a specific deficit in inflectional morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study that investigated the accuracy of grammatical number inflection produced by 60 Jordanian Arabic‐speaking children and young adults with Down syndrome showed that children with Down syndrome scored lower in dual and plural forms in nouns than in singular form (Mashaqba et al., 2020). However, in their study, Ring and Clahsen (2005) found that English‐speaking adolescents with Down syndrome (aged 12–14 years) who performed several elicitation tasks on past tense and noun plural inflection displayed no signs of a specific deficit with inflectional morphology.…”
Section: Introductionmentioning
confidence: 99%
“…This will have a noticeable impact on children's progress in several aspects, such as adult control in spelling and reading tasks. Additionally, the results should be taken into consideration by parents, caregivers and language therapists/clinicians when preparing appropriate exercises, linguistic training, and treatment for children with speech disorders as early as possible, because age has a significant influence on the linguistic performance of children (Mashaqba, Abu Sa'aleek, Huneety and Al-Shboul 2020). Speech therapy clinicians mainly use perceptual judgment when dealing with impaired children (such as children with cleft palate, Down syndrome, stuttering, and hearing impairment) in their therapy sessions, which is insufficient.…”
Section: Discussionmentioning
confidence: 99%